KARAKTERISTIK LINGKUNGAN PERAIRAN KEPULAUAN SERIBU - Sachoemar, Suhendar I (Jurnal Air Indonesia, 2008)
An identification of the environment characteristics of the Seribu Islands was conducted by using the physical and chemical data obtained from various sources. The characteristics of the water quality at the Seribu Island was identified as a moderate level in the middle part and better in the northern part. While in the southern part was poor due to the effect of the degraded water quality at Jakarta Bay as indicated by low transparency and high heavy metal concentration of the Cd and Pb. Keywords : Karakteristik lingkungan perairan, Kepulauan Seribu